Determination of Fit to Work Status for Thyroid Cancer Survivor: A Case Study in Occupational Health Setting - Hardy, Syaifoel; Tukayo, Isak Jurun Hans; Fahruddin, Akhir; Afzal, Ridha (Journal of Public Health for Tropical and Coastal Region, 2022)
Introduction: A thyroid cancer worker after undergoing ablation procedure requires specific recommendation when return to work. This study aims to determine a framework of the fitness to work (FTW) status from the occupational health nursing viewpoint. The implication is to help answer the question whether the worker is fit to work as a cancer survivor.Methods: This study used a Case Study method with descriptive design. The sample was a therapist associate whose scope of work was office-based. The method applied the Test Blueprint of case management assessment by the American Board of Occupational Health Nursing (ABOHN) standard combined with the Glasgow Coma Scale (GCS) after the ablation procedure as the instrument. We analyzed the case with The Fit to Work (FTW) Model of Hybrid Model.Results: FTW  assessment showed vital signs within normal limits. Immunological examination found abnormalities. The left and right thyroid lobes were not visualized and there was no mass in the surgical bed. The client was advised for specialist follow up after 6 months. After the ablation procedure, the employee had a verbal communication disorder. The Glasgow Coma Scale (GCS) recorded point 5 hoarseness with decreased tone quantity was about 90%. Based on the medical report and his specialist’s advice, 6 months after ablation the employee’s medical condition showed improvement.Conclusion: With the At-Will Model of Hybrid as the framework to determine the fitness status, we recommended to declare him fit with restrictions and advised for regular fitness status update.